OPTIMASI EFISIENSI PAKAN DAN PERTUMBUHAN IKAN KAKAP PUTIH (Lates calcarifer) MELALUI KOMBINASI PAKAN KOMERSIAL DAN IKAN LEMURU PADA SISTEM KERAMBA JARING APUNG - Diyo Wahyu Ardiansyah; Gede Ari Yudasmara; Hamdanul Fain (Universitas Mataram, 2026)
High feed costs remain a major constraint in the cultivation of Asian seabass (Lates calcarifer) in floating net cages (FNC), necessitating a more efficient feeding strategy without compromising fish growth performance. This study aims to analyze the effect of a combination of commercial feed and lemuru fish (Sardinella longiceps) on the feed efficiency and growth of Asian seabass, as well as to determine the most optimal feed combination. The research employed an experimental method utilizing a Randomized Block Design (RBD) consisting of three treatments and three replications: Treatment A (100% commercial feed), Treatment B (75% commercial feed + 25% lemuru fish), and Treatment C (50% commercial feed + 50% lemuru fish). The observed parameters included absolute length growth, absolute weight growth, specific growth rate (SGR), feed conversion ratio (FCR), survival rate (SR), and water quality. Data were analyzed using Analysis of Variance (ANOVA) at a 95% confidence level, followed by the Least Significant Difference (LSD) test. The results indicated that the feed combinations significantly affected growth and feed efficiency (p < 0.05). Treatment B yielded the best performance with an absolute length growth of 5.07 cm, an absolute weight growth of 50.5 g, an SGR of 2.225% per day, and the lowest FCR of 1.877 g/g. The fish survival rate ranged from 90% to 93%, while water quality parameters remained within the optimal range throughout the study. Therefore, the combination of 75% commercial feed and 25% lemuru fish is the most effective formulation for improving the feed efficiency and growth of Asian seabass in the floating net cage system.